Exploring the pathway between family chaos, stress reactivity, and emotion regulation - Najman, Jonathan I., author; Lucas-Thompson, Rachel, advisor; MacPhee, Dave, committee member; Faw, Meara, committee member (Colorado State University. Libraries, 2024)
Family chaos is the cumulative exposure to disorienting environments (Fiese & Winter, 2010), and is associated with poor academic outcomes, health problems, and adjustment problems (e.g., Evans & Kim, 2013). Two distinguishable elements of family chaos are a) instability, or unpredictable events that disrupt continuity of the household, and b) disorganization, or enduring experiences that contribute to overwhelming disorder (Garrett-Peters et al., 2019). Although a relatively new distinction, it appears critical, in that instability is a stronger predictor of executive functioning than disorganization (Andrews et al., 2021). Our goal was to provide an investigation of this model to other key outcomes: stress reactivity and emotion regulation. A total of 153 adolescents (10-17yrs) completed the stress test and reported emotion regulation (Zeman et al., 2001; Garnefski et al., 2001). Family instability was significantly but weakly associated with disorganization, r = .16, r2 = .03, p < .05. Generalized Estimating Equations controlling for age, income, and race revealed that family instability, but not disorganization, significantly negatively predicted cortisol reactivity (b= -4.65, SE= 4.17, p<.05). The distinction of family chaos into instability and disorganization requires further research to elucidate the relationship between family chaos and poor developmental outcomes.
Keywords: disorganization; family chaos; stress reactivity; emotional regulation; adolescence; instability